2016
DOI: 10.1177/0892705716646417
|View full text |Cite
|
Sign up to set email alerts
|

Properties of rigid polyvinyl chloride foam composites reinforced with different shape fillers

Abstract: In this study, the effect of reinforcements' shape and type on the mechanical, thermal, and morphological properties of polyvinyl chloride (PVC) foam composites is investigated. For this purpose, three different fillers, longitudinal structure glass fiber, flaky structure mica, and spherical structure fly ash, were selected to prepare PVC foam composites with 0-20 wt% loading. The tensile strength in both 10 wt% reinforced mica and glass fiber composites improved slightly, while it decreased with the addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…A similar result was stated by Khoshnoud et al (2017). The reinforcements have a stronger tendency to agglomerate due to their high aspect ratio and low surface energy [ 32 ]. According to Kumar et al (2018), the filler molecules agglomeration around the matrix, which precludes proper curing of the composites and results in a reduction in the flexural and tensile behaviour of the composites at a higher percentage of filler [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similar result was stated by Khoshnoud et al (2017). The reinforcements have a stronger tendency to agglomerate due to their high aspect ratio and low surface energy [ 32 ]. According to Kumar et al (2018), the filler molecules agglomeration around the matrix, which precludes proper curing of the composites and results in a reduction in the flexural and tensile behaviour of the composites at a higher percentage of filler [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…As observed from many research, FA could effectively reinforce with r‐PVC matrix while increasing its physicomechanical and thermal characteristics. Patil et al, reported that PVC/FA matrix composite manufacturing by solution casting method which shows improvement in the ductility and flame retardancy properties of PVC 9–11 . Also, in recent study of r‐PVC/FA composite, it is observed that the composites prepared using 30 wt% loading of FA showed an enhancement in tensile strength to 42%, tensile modulus to 29%, and impact strength to 159% 12 .…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, PVC products including RPVC foams upon burning release amounts of smoke and toxic gases, which are threats to human health and environment 6 . According to the previous reports, 7,8 inorganic fillers including fly ash, mica, glass fiber and clay have been applied for RPVC foam reinforcement and toughening, while the flame retardancy and smoke suppression of the RPVC foam were not investigated. You et al 9 applied copper (Cu) and molybdenum trioxide (MoO 3 ) in RPVC foams and found that the RPVC foam containing 1 phr Cu and 4 phr MoO 3 showed an 27% reduction in smoke density compared with pure RPVC foam, whereas the mechanical performances were not reported.…”
Section: Introductionmentioning
confidence: 99%